Porous silicon-carbon composite material for negative electrode of lithium ion battery and preparation method of porous silicon-carbon composite material

By using porous silicon-carbon composite materials in lithium-ion batteries, the problem of poor volume expansion and conductivity of silicon negative electrode materials during lithium deintercalation is solved, and higher voltage resistance and cycle life are achieved.

CN119673990APending Publication Date: 2025-03-21BERZELIUS (NANJING) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747922.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries causes severe volume expansion and poor conductivity during the deintercalation of lithium, resulting in poor circulation performance and Coulomb efficiency.

Method used

Porous silicon-carbon composite material is used as the negative electrode material of lithium-ion battery. By forming an alumina film on the porous carbon substrate and infiltrating silicon particles, and then covering a carbon layer to form a porous silicon-carbon composite material.

Benefits of technology

Through the combination of alumina film and carbon layer, the pressure resistance and conductivity of the material are significantly improved, the expansion of silicon particles is reduced, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673990A_ABST
    Figure CN119673990A_ABST
Patent Text Reader

Abstract

The invention discloses a porous silicon-carbon composite material for a negative electrode of a lithium ion battery and a preparation method thereof, the porous silicon-carbon composite material comprises porous silicon-carbon particles and a coating layer coating the surfaces of the porous silicon-carbon particles, and the porous silicon-carbon particles are formed by dispersedly distributing silicon particles on a porous carbon base material with an aluminum oxide film in pores; and the coating layer is a carbon layer. The aluminum oxide film layer in the holes of the silicon-carbon composite material improves the particle hardness, improves the pressure resistance of the material, improves the electrochemical expansion of the material, and improves the electrochemical cycle performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a porous silicon-carbon composite material for a lithium ion battery negative electrode and a preparation method thereof. Background Art

[0002] Throughout the history of battery development, lithium-ion batteries, as a major form of new energy, have received widespread attention and developed rapidly because of their high volume-to-energy and mass-to-energy ratios, rechargeability, and pollution-free. At present, the development of the telecommunications and information markets, especially the extensive use of mobile phones and laptops, has brought market opportunities to lithium-ion batteries. Today, lithium-ion batteries are widely used in the consumer electronics field and the electric vehicle industry, affecting almost everyone's life.

[0003] As people's requirements for battery energy density are getting higher and higher, traditional lithium-ion batteries can no longer meet people's requirements, and high energy density batteries have received more and more attention. The energy density of lithium-ion batteries mainly depends on the positive and negative electrode materials of the battery. The improvement and development of positive and negative electrode materials are the key to improving battery energy density. Graphite, as a traditional lithium-ion negative electrode material, has been widely used in various industries because of its high cycle efficiency and good cycle performance. However, its theoretical capacity is only 372mAh / g, which can no longer meet people's requirements for high energy density. Therefore, the development of new high energy density negative electrode materials has become a key technology to improve lithium-ion batteries.

[0004] Compared with traditional carbon negative electrode materials, silicon materials have a theoretical capacity of up to 4200mAh / g, and their lithium insertion potential is low (less than 0.5V) and has higher safety performance. Therefore, silicon negative electrode materials have received more and more attention in recent years, and people's research on silicon negative electrode materials has become more and more in-depth. However, silicon negative electrode materials produce serious volume expansion after the lithium insertion and extraction process, with an expansion rate of up to about 300%. And the conductivity of silicon materials is poor, which is not conducive to the extraction and extraction of lithium ions. At the same time, an unstable SEI film is continuously formed on the surface of the silicon negative electrode during the lithium extraction and extraction process, so the silicon negative electrode material exhibits poor cycle performance and Coulomb efficiency. Therefore, the improvement of silicon materials has become the key to its application. At present, there are two main directions for the improvement of silicon materials. The first is to reduce the size of silicon particles, reduce the internal stress of particles, and reduce the volume change of particles. However, after the silicon particles are nano-sized, SEI films are continuously formed during the lithium extraction and extraction process, which is not conducive to the cycle performance of the battery. The second is to coat or dope silicon materials with elements, which not only improves the conductivity of the material, but also forms a "buffer skeleton" in the silicon material. This structure can disperse the stress caused by volume change during the lithium insertion and extraction process of the silicon material. Porous carbon is widely used as a substrate for silicon-carbon materials. It has a porous structure, but has poor pressure resistance. Summary of the invention

[0005] In order to solve the problems of poor conductivity, large expansion and poor cycle of silicon in the semiconductor mentioned above in lithium ion battery applications, the present invention provides a porous silicon-carbon composite material for lithium ion battery negative electrode and a preparation method thereof.

[0006] The porous silicon-carbon composite material for lithium-ion battery negative electrode of the present invention comprises porous silicon-carbon particles and a coating layer coated on the surface of the porous silicon-carbon particles, wherein the porous silicon-carbon particles are formed by silicon particles dispersedly distributed on a porous carbon substrate having an aluminum oxide film in the pores; the coating layer is a carbon layer. The porous silicon-carbon composite material is a primary particle or a secondary particle composed of primary particles; and the coating layer is a layer of amorphous carbon.

[0007] The particle size of the porous silicon-carbon composite material for the negative electrode of the lithium-ion battery is 0.1-20 μm, the mass percentage of silicon is 5%-70%, the mass percentage of the aluminum oxide film is 0.01%-8%, and the thickness of the coating layer is 1-1000 nm.

[0008] Preferably, the particle size of the porous silicon-carbon composite material for lithium-ion battery negative electrode is 0.3-18 μm, the mass percentage of silicon is 8%-65%, the mass percentage of aluminum oxide film is 0.02%-7%, and the thickness of the coating layer is 2-800 nm.

[0009] More preferably, the particle size of the porous silicon-carbon composite material for lithium-ion battery negative electrode is 0.5-16 μm, the mass percentage of silicon is 10%-60%, the mass percentage of aluminum oxide film is 0.1%-6%, and the thickness of the coating layer is 5-500 nm.

[0010] The present invention also provides a method for preparing the above-mentioned porous silicon-carbon composite material for lithium ion battery negative electrode, comprising the following steps: (1) placing a porous carbon substrate in a vapor deposition furnace;

[0011] (2) under an inert protective gas flow, the temperature is increased and then maintained, an aluminum-containing precursor is first introduced into the vapor deposition furnace, an aluminum oxide film is formed in the pores of the porous carbon substrate, and then a silicon-containing precursor is introduced to continue to infiltrate silicon particles in the pores to obtain porous silicon-carbon particles;

[0012] (3) continuing to increase the temperature and then maintaining the temperature, introducing a carbon-containing precursor to coat the surface of the porous silicon-carbon particles with a carbon layer;

[0013] (4) After the temperature drops to room temperature, the material is discharged and screened and demagnetized.

[0014] In step (2), the inert protective gas is one or more of nitrogen, argon, helium, neon or krypton; the insulation temperature is 400°C-1000°C; the aluminum-containing precursor is one or more of aluminum acetylacetonate, triethylaluminum, triisobutylaluminum; the silicon-containing precursor is a silicon-containing gas selected from one or more of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, tetrachlorosilane; in step (3), the insulation temperature is 400°C-1000°C; the carbon-containing precursor is selected from one or more of methane, ethane, propane, butane, acetylene and propylene.

[0015] The present invention also provides an electrode, which includes the above-mentioned porous silicon-carbon composite material for lithium ion battery negative electrode or the porous silicon-carbon composite material for lithium ion battery negative electrode prepared using the above-mentioned preparation method of the porous silicon-carbon composite material for lithium ion battery negative electrode.

[0016] The present invention also provides a battery, which comprises the above-mentioned electrode.

[0017] Beneficial effect: The aluminum oxide film layer inside the porous silicon-carbon composite material for the negative electrode of the lithium-ion battery of the present invention can greatly prevent the corrosion of the electrolyte and can accommodate the particles in the Li + The volume change during the intercalation and deintercalation process prevents damage to the electrode structure, thereby extending the battery cycle performance of the material. The porous structure of the porous silicon-carbon substrate itself is not conducive to the pressure resistance of the material. The silicon-carbon material obtained by forming a nano-thick aluminum oxide film in the porous carbon and then infiltrating silicon fills the pores, which can significantly improve the pressure resistance of the material. The carbon skeleton provided by the porous carbon substrate has excellent conductivity, which can improve the conductivity of the overall silicon-carbon material. The porous carbon skeleton can also provide expansion space for the silicon material, effectively reducing the expansion of silicon particles. In addition, the surface of this porous silicon-carbon composite material is coated with a layer of amorphous carbon, which can also effectively buffer the stress generated by the volume expansion of the silicon material during the intercalation and deintercalation of lithium. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the structure of the porous silicon-carbon composite material for the negative electrode of a lithium ion battery of the present invention;

[0019] In the figure, 1. porous carbon substrate; 2. aluminum oxide film; 3. silicon particles; 4. carbon coating layer. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below by way of examples, but the present invention is not limited to the examples.

[0021] The present invention is a porous silicon-carbon composite material for a negative electrode of a lithium-ion battery, comprising porous silicon-carbon particles and a coating layer coated on the surface of the porous silicon-carbon particles, wherein the porous silicon-carbon particles are silicon particles 3 dispersedly distributed on a porous carbon substrate 1 having an aluminum oxide film 2 in the pores; and the coating layer is a carbon coating layer 4. The porous silicon-carbon composite material for a negative electrode of a lithium-ion battery of the present invention is prepared by the following steps:

[0022] (1) placing a certain mass of porous carbon substrate 1 in a vapor deposition furnace;

[0023] (2) Continuously filling a certain flow rate of inert protective gas into the vapor deposition furnace;

[0024] (3) adjusting the speed of the vapor deposition furnace to drive the porous carbon substrate 1 to rotate together;

[0025] (4) starting the furnace chamber heating system to heat the vapor deposition furnace;

[0026] (5) When the first deposition temperature is reached and the temperature is maintained, a certain flow rate of an aluminum-containing precursor is introduced into the vapor deposition furnace, and after a layer of aluminum oxide film 2 is deposited in the porous structure of the porous carbon substrate 1, the introduction of the aluminum-containing precursor is stopped, and a certain flow rate of a silicon-containing precursor is introduced to continue to infiltrate silicon particles 3 in the pores until the deposition is completed, and the introduction of the silicon-containing precursor is stopped to obtain porous silicon-carbon particles;

[0027] (6) continuing to raise the temperature to the second deposition temperature and maintaining the temperature, continuously introducing a certain flow rate of carbon-containing precursor to coat the surface of the porous silicon-carbon particles with a carbon layer, until the deposition is completed, and stopping introducing the carbon-containing precursor;

[0028] (7) After the temperature drops to room temperature, the material is discharged, sieved and demagnetized to obtain a porous silicon-carbon composite material having an aluminum oxide film 2 structure.

[0029] In step (1), the vapor deposition furnace is a CVD vapor deposition furnace or a fluidized bed.

[0030] In step (2), the inert protective gas is one or more of nitrogen, argon, helium, neon or krypton, and the flow rate is 1 to 100 L / min, preferably 2 to 90 L / min, and more preferably 5 to 80 L / min.

[0031] In step (3), the rotation speed of the vapor deposition furnace is 1 to 50 Hz, preferably 5 to 45 Hz, and more preferably 10 to 40 Hz.

[0032] In step (4), the heating rate is 1 to 10°C / min.

[0033] In step (5), the first deposition temperature (holding temperature) is 400°C to 1000°C, preferably 420°C to 900°C, and more preferably 450°C to 800°C; the holding time is 1 to 15 hours, preferably 1.5 to 14 hours, and more preferably 2 to 14 hours; the flow rate of the aluminum-containing precursor is 0.01 to 20 L / min, preferably 0.05 to 15 L / min, and more preferably 0.1 to 10 L / min; the aluminum-containing precursor is one or more of acetylacetonate aluminum, triethylaluminum, and triisobutylaluminum; the flow rate of the silicon-containing precursor is 0.01 to 30 L / min, preferably 0.1 to 25 L / min, and more preferably 1 to 20 L / min; the silicon-containing precursor is one or more of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.

[0034] In step (6), the heating rate when the temperature continues to rise is 1 to 10°C / min, the second deposition temperature (holding temperature) is 400°C to 1000°C, preferably 450°C to 900°C, and more preferably 550°C to 850°C; the holding time is 1 to 10 hours, preferably 1.5 to 8 hours, and more preferably 2 to 6 hours; the flow rate of the carbon-containing precursor is 0.01 to 30 L / min, preferably 0.1 to 25 L / min, and more preferably 1 to 20 L / min; the carbon-containing precursor is selected from one or more of methane, ethane, propane, butane, acetylene and propylene.

[0035] In step (7), screening is performed using any one of a vibrating screen and an air flow classifier.

[0036] Example 1

[0037] Weigh 1.5kg of porous carbon substrate 1 with a median particle size of 7μm and load it into the CVD vapor deposition furnace. Fill the CVD vapor deposition furnace with protective gas argon and adjust the argon flow rate to 5L / min. Adjust the speed of the CVD vapor deposition furnace to 25Hz to drive the porous carbon substrate 1 to rotate together. When the CVD vapor deposition furnace starts to rotate, start the furnace chamber heating system, heat the deposition furnace, set the heating rate to 2℃ / min, the first deposition temperature to 450℃, and the deposition (insulation) time to 2h. When the temperature reaches the first deposition temperature, aluminum acetylacetonate is first introduced into the furnace chamber at a flow rate of 0.1L / min, and the introduction of aluminum acetylacetonate is stopped after 0.5h, and then monosilane is introduced at a flow rate of 1L / min for 1.5h, and monosilane is stopped after the insulation is completed. The protective gas argon is continuously introduced, and the furnace body continues to heat up. The heating rate is set to 2°C / min, the second deposition temperature is 550°C, and the deposition (insulation) time is 2h. When the temperature reaches the second deposition temperature, acetylene is introduced into the furnace chamber at a flow rate of 1L / min for 2h. After the deposition is completed and the temperature drops to room temperature, the furnace body is opened, and the porous silicon-carbon composite material is sieved and demagnetized using a vibrating screen. The structure of the porous silicon-carbon composite material is as follows Figure 1 As shown, that is, the pores of the porous carbon substrate 1 are completely covered with an aluminum oxide film 2, and silicon particles 3 are dispersed on the aluminum oxide film 2 in the pores, and then the whole is coated with a carbon coating layer 4.

[0038] The following equipment was used to characterize the porous silicon-carbon composite material prepared above.

[0039] The aluminum content was detected by inductively coupled plasma optical emission spectrometry (Agilent 5800ICP-OES, Agilent).

[0040] The carbon content was detected by an ELEMENTRAC CS-i carbon-sulfur analyzer, and the silicon content was calculated according to the carbon content and the alumina content (Si Wt%=100%-C Wt%-Al2O3 Wt%).

[0041] The thickness of the carbon coating layer was measured using a Hitachi HT7700 transmission electron microscope.

[0042] The particle size was measured using Bettersize 2600 produced by Dandong Better Instruments.

[0043] BET was tested using a BSD-BET400 specific surface area tester.

[0044] The material was compacted with a pressure of 379 MPa using a MiQi MZD-20 fully automatic tablet press. The BET of the material before and after compaction was tested to test the pressure resistance of the material.

[0045] Half-cell performance test: Take 95 parts of the above-mentioned porous silicon-carbon composite material, 2.5 parts of conductive additives, and 2.5 parts of binders, homogenize, coat, dry, and roll in an aqueous system to obtain a porous silicon-carbon negative electrode. The above-mentioned porous silicon-carbon negative electrode, diaphragm, lithium sheet, and stainless steel gasket are stacked in sequence and sealed after adding 200μL of electrolyte to form a 2016-type lithium-ion half-cell. The capacity and discharge efficiency are tested using the small (micro) current range equipment of Wuhan Blue Electric Electronics Co., Ltd.

[0046] The test results show that the particle size of the porous silicon-carbon composite material is 7.1μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 0.01%, the mass percentage of the silicon element is 5%, and the thickness of the carbon coating layer 4 is 1nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1090mAh / g, the first discharge efficiency of the half-cell is 90.8%, the full charge expansion is 85%, and the retention rate after 30 cycles is 75%; the initial BET of the material is 5.1m 2 / g, after compaction at 379Mpa, BET is 51.3m 2 / g, and the results are shown in Table 1.

[0047] Example 2

[0048] Compared with Example 1, the difference is that the protective gas argon flow rate is 10L / min, the first deposition temperature is 460°C, the total deposition (heat preservation) time is 2.8h, the aluminum acetylacetonate flow rate is 1L / min, the time is 0.8h, the monosilane flow rate is 3L / min, and the time is 2h. The second deposition temperature is 560°C, the deposition (heat preservation) time is 2.5h, and the acetylene flow rate is 3L / min.

[0049] The test results show that the particle size of the porous silicon-carbon composite material is 7.3μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 0.1%, the mass percentage of the silicon element is 10%, and the thickness of the carbon coating layer 4 is 8nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1285mAh / g, the first discharge efficiency of the half-cell is 91.1%, the full charge expansion is 80%, and the retention rate after 30 cycles is 76%. The initial BET of the material is 4.5m 2 / g, after compaction at 379Mpa, BET is 32.7m 2 / g, and the results are shown in Table 1.

[0050] Example 3

[0051] Compared with Example 1, the difference is that the protective gas argon flow rate is 15 L / min, the first deposition temperature is 470°C, the total deposition (holding) time is 3.7 h, the aluminum acetylacetonate flow rate is 2 L / min, the time is 1.2 h, the monosilane flow rate is 5 L / min, and the time is 2.5 h. The second deposition temperature is 570°C, the deposition (holding) time is 2.5 h, and the acetylene flow rate is 5 L / min.

[0052] The test results show that the particle size of the porous silicon-carbon composite material is 7.2μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 0.6%, the mass percentage of the silicon element is 20%, and the thickness of the carbon coating layer 4 is 20nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1481mAh / g, the first discharge efficiency of the half-cell is 91.4%, the full charge expansion is 78%, and the retention rate after 30 cycles is 78%. The initial BET of the material is 3.6m 2 / g, after compaction at 379Mpa, BET is 16.1m 2 / g, and the results are shown in Table 1.

[0053] Example 4

[0054] Compared with Example 1, the difference is that the protective gas argon flow rate is 20L / min, the first deposition temperature is 480°C, the total deposition (holding) time is 4.5h, the aluminum acetylacetonate flow rate is 3L / min, the time is 1.5h, the monosilane flow rate is 7L / min, and the time is 3h. The second deposition temperature is 580°C, the deposition (holding) time is 3h, and the acetylene flow rate is 7L / min.

[0055] The test results show that the particle size of the porous silicon-carbon composite material is 7.1μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 1.0%, the mass percentage of the silicon element is 35%, and the thickness of the carbon coating layer 4 is 40nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1735mAh / g, the first discharge efficiency of the half-cell is 91.8%, the full charge expansion is 75%, and the retention rate after 30 cycles is 81%. The initial BET of the material is 3.1m 2 / g, after compaction at 379Mpa, BET is 9.6m 2 / g, and the results are shown in Table 1.

[0056] Example 5

[0057] Compared with Example 1, the difference is that the protective gas argon flow rate is 25 L / min, the first deposition temperature is 490°C, the total deposition (holding) time is 5 h, the aluminum acetylacetonate flow rate is 4 L / min, the time is 1.5 h, the monosilane flow rate is 9 L / min, and the time is 3.5 h. The second deposition temperature is 590°C, the deposition (holding) time is 3 h, and the acetylene flow rate is 9 L / min.

[0058] The test results show that the particle size of the porous silicon-carbon composite material is 7.3μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 1.2%, the mass percentage of the silicon element is 40%, and the thickness of the carbon coating layer 4 is 60nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1760mAh / g, the first discharge efficiency of the half-cell is 92.1%, the full charge expansion is 60%, and the retention rate after 30 cycles is 84%. The initial BET of the material is 2.3m 2 / g, after compaction at 379Mpa, BET is 6.1m 2 / g, and the results are shown in Table 1.

[0059] Example 6

[0060] Compared with Example 1, the difference is that the protective gas argon flow rate is 30 L / min, the first deposition temperature is 500°C, the total deposition (holding) time is 5.5 h, the aluminum acetylacetonate flow rate is 5 L / min, the time is 1.5 h, the monosilane flow rate is 11 L / min, and the time is 4 h. The second deposition temperature is 600°C, the deposition (holding) time is 3 h, and the acetylene flow rate is 11 L / min.

[0061] The test results show that the particle size of the porous silicon-carbon composite material is 7.2μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 1.5%, the mass percentage of the silicon element is 45%, and the thickness of the carbon coating layer 4 is 70nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1883mAh / g, the first discharge efficiency of the half-cell is 93.7%, the full charge expansion is 50%, and the retention rate after 30 cycles is 87%. The initial BET of the material is 1.8m 2 / g, after compaction at 379Mpa, BET is 3.2m 2 / g, and the results are shown in Table 1.

[0062] Example 7

[0063] Compared with Example 1, the difference is that the protective gas argon flow rate is 35 L / min, the first deposition temperature is 520°C, the total deposition (holding) time is 6 h, the aluminum acetylacetonate flow rate is 6 L / min, the time is 1.5 h, the monosilane flow rate is 13 L / min, and the time is 4.5 h. The second deposition temperature is 650°C, the deposition (holding) time is 4 h, and the acetylene flow rate is 13 L / min.

[0064] The test results show that the particle size of the porous silicon-carbon composite material is 7.3μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 2%, the mass percentage of the silicon element is 52%, and the thickness of the carbon coating layer 4 is 80nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 2030mAh / g, the first discharge efficiency of the half-cell is 94.4%, the full charge expansion is 40%, and the retention rate after 30 cycles is 90%. The initial BET of the material is 1.2m 2 / g, after compaction at 379Mpa, BET is 1.5m 2 / g, and the results are shown in Table 1.

[0065] Example 8

[0066] Compared with Example 1, the difference is that the protective gas argon flow rate is 40 L / min, the first deposition temperature is 560°C, the total deposition (holding) time is 7h, the aluminum acetylacetonate flow rate is 7L / min, the time is 2h, the monosilane flow rate is 15L / min, and the time is 5h. The second deposition temperature is 700°C, the deposition (holding) time is 5h, and the acetylene flow rate is 15L / min.

[0067] The test results show that the particle size of the porous silicon-carbon composite material is 7.4μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 3%, the mass percentage of the silicon element is 55%, and the thickness of the carbon coating layer 4 is 100nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 2015mAh / g, the first discharge efficiency of the half-cell is 93.3%, the full charge expansion is 45%, and the retention rate after 30 cycles is 87%. The initial BET of the material is 1.5m 2 / g, after compaction at 379Mpa, BET is 3.2m 2 / g, and the results are shown in Table 1.

[0068] Example 9

[0069] Compared with Example 1, the difference is that the protective gas argon flow rate is 50 L / min, the first deposition temperature is 600°C, the total deposition (holding) time is 8 hours, the aluminum acetylacetonate flow rate is 8 L / min, the time is 2.5 hours, the monosilane flow rate is 17 L / min, and the time is 5.5 hours. The second deposition temperature is 750°C, the deposition (holding) time is 5 hours, and the acetylene flow rate is 17 L / min.

[0070] The test results show that the particle size of the porous silicon-carbon composite material is 7.3μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 4%, the mass percentage of the silicon element is 60%, and the thickness of the carbon coating layer 4 is 200nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 2019mAh / g, the first discharge efficiency of the half-cell is 92.1%, the full charge expansion is 50%, and the retention rate after 30 cycles is 83%. The initial BET of the material is 1.6m 2 / g, after compaction at 379Mpa, BET is 5.8m 2 / g, and the results are shown in Table 1.

[0071] Example 10

[0072] Compared with Example 1, the difference is that the protective gas argon flow rate is 60 L / min, the first deposition temperature is 700°C, the total deposition (holding) time is 9 h, the aluminum acetylacetonate flow rate is 9 L / min, the time is 3 h, the monosilane flow rate is 19 L / min, and the time is 6 h. The second deposition temperature is 800°C, the deposition (holding) time is 5 h, and the acetylene flow rate is 19 L / min.

[0073] The test results show that the particle size of the porous silicon-carbon composite material is 7.3μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 5%, the mass percentage of the silicon element is 65%, and the thickness of the carbon coating layer 4 is 500nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 2021mAh / g, the first discharge efficiency of the half-cell is 91.2%, the full charge expansion is 60%, and the retention rate after 30 cycles is 79%. The initial BET of the material is 1.9m 2 / g, after compaction at 379Mpa, BET is 9.3m 2 / g, and the results are shown in Table 1.

[0074] Embodiment 11

[0075] Compared with Example 1, the difference is that the protective gas argon flow rate is 80 L / min, the first deposition temperature is 800°C, the total deposition (insulation) time is 12 h, the aluminum acetylacetonate flow rate is 10 L / min, the time is 4 h, the monosilane flow rate is 20 L / min, the time is 8 h. The second deposition temperature is 850°C, the deposition (insulation) time is 6 h, and the acetylene flow rate is 20 L / min.

[0076] The test results show that the particle size of the porous silicon-carbon composite material is 7.4μm, the mass percentage of the aluminum oxide film 2 in the porous silicon-carbon composite material is 8%, the mass percentage of the silicon element is 70%, and the thickness of the carbon coating layer 4 is 1000nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 2032mAh / g, the first discharge efficiency of the half-cell is 90.5%, the full charge expansion is 70%, and the retention rate after 30 cycles is 75%. The initial BET of the material is 2m 2 / g, after compaction at 379Mpa, BET is 14.9m 2 / g, and the results are shown in Table 1.

[0077] Comparative Example 1

[0078] Compared with Example 1, the difference is that the flow rate of protective gas argon is 20 L / min, the first deposition temperature is 480°C, no aluminum acetylacetonate is introduced, the flow rate of monosilane is 7 L / min, and the time is 3 h. The second deposition temperature is 580°C, the deposition (heat preservation) time is 3 h, and the acetylene flow rate is 7 L / min.

[0079] The test results show that the particle size of the porous silicon-carbon composite material is 7.2μm, the mass percentage of silicon is 38%, and the thickness of the carbon coating layer is 39nm; the first cycle lithium removal capacity of the half-cell prepared by this material is 1685mAh / g, the first discharge efficiency of the half-cell is 90.1%, the full charge expansion is 88%, and the retention rate after 30 cycles is 61%. The initial BET of the material is 4.4m 2 / g, after compaction at 379Mpa, BET is 102.1m 2 / g, and the results are shown in Table 1.

[0080] Table 1 Performance data of porous silicon-carbon composite materials and half-cells

[0081]

[0082] It can be seen from Table 1 that the porous silicon-carbon material prepared after porous carbon infiltration with silicon has the advantages of high capacity and high efficiency. The aluminum oxide film layer can effectively improve the pressure resistance of the material and improve the expansion performance of the material.

[0083] The above-mentioned technologies not specifically mentioned are all referred to the prior art.

[0084] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A porous silicon-carbon composite material for a negative electrode of a lithium-ion battery, characterized in that: The invention comprises porous silicon-carbon particles and a coating layer coated on the surface of the porous silicon-carbon particles. The porous silicon-carbon particles are formed by silicon particles dispersedly distributed on a porous carbon substrate with an aluminum oxide film in the pores; and the coating layer is a carbon layer.

2. The porous silicon-carbon composite material for lithium-ion battery negative electrode according to claim 1, characterized in that: The particle size of the porous silicon-carbon composite material for the negative electrode of a lithium-ion battery is 0.1-20 μm, the mass percentage of silicon is 5%-70%, the mass percentage of the aluminum oxide film is 0.01%-8%, and the thickness of the coating layer is 1-1000 nm.

3. The porous silicon-carbon composite material for lithium-ion battery negative electrode according to claim 2, characterized in that: The particle size of the porous silicon-carbon composite material for the negative electrode of a lithium-ion battery is 0.3-18 μm, the mass percentage of silicon is 8%-65%, the mass percentage of the aluminum oxide film is 0.02%-7%, and the thickness of the coating layer is 2-800 nm.

4. The porous silicon-carbon composite material for a negative electrode of a lithium-ion battery according to claim 3, characterized in that: The particle size of the porous silicon-carbon composite material for the negative electrode of a lithium-ion battery is 0.5-16 μm, the mass percentage of silicon is 10%-60%, the mass percentage of the aluminum oxide film is 0.1%-6%, and the thickness of the coating layer is 5-500 nm.

5. The method for preparing the porous silicon-carbon composite material for lithium ion battery negative electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Loading a porous carbon substrate into a vapor deposition furnace; (2) Under an inert protective gas flow, the temperature is increased and then maintained, and an aluminum-containing precursor is first introduced into the vapor deposition furnace to form an aluminum oxide film in the pores of the porous carbon substrate, and then a silicon-containing precursor is introduced to continue to infiltrate silicon particles in the pores to obtain porous silicon-carbon particles; (3) continuing to increase the temperature and then maintaining the temperature, introducing a carbon-containing precursor to coat the surface of the porous silicon-carbon particles with a carbon layer; (4) After the temperature drops to room temperature, the material is discharged and screened and demagnetized.

6. The method for preparing the porous silicon-carbon composite material for lithium ion battery negative electrode according to claim 5, characterized in that: In step (2), the inert protective gas is one or more of nitrogen, argon, helium, neon or krypton; the insulation temperature is 400°C-1000°C; the aluminum-containing precursor is one or more of aluminum acetylacetonate, triethylaluminum, triisobutylaluminum; the silicon-containing precursor is a silicon-containing gas selected from one or more of monosilane, disilane, trisilane, dichlorosilane, trichlorosilane, tetrachlorosilane; in step (3), the insulation temperature is 400°C-1000°C; the carbon-containing precursor is selected from one or more of methane, ethane, propane, butane, acetylene and propylene.

7. An electrode, characterized in that: The invention relates to a porous silicon-carbon composite material for a negative electrode of a lithium-ion battery comprising any one of claims 1 to 4 or a porous silicon-carbon composite material for a negative electrode of a lithium-ion battery prepared by the method for preparing the porous silicon-carbon composite material for a negative electrode of a lithium-ion battery according to claim 5 or 6.

8. A battery, characterized in that: Comprising the electrode according to claim 7.